Long-term humoral immunity induced by CVC1302-adjuvanted serotype O foot-and-mouth disease inactivated vaccine correlates with promoted T follicular helper cells and thus germinal center responses in mice. Issue 51 (18th December 2017) - Du, Luping; Chen, Jin; Hou, Liting; Yu, Xiaoming; Zheng, Qisheng; Hou, Jibo
Highlights: CVC1302 adjuvanticity is mediated through potent induction of GC responses. CVC1302 adjuvanticity is mediated through the induction of TFH cells. CVC1302 adjuvanticity is mediated through master regulators of B cell identity. Abstract: Long-lasting humoral immunity is one of the necessary criteria for a successful vaccine. In our previous study, it was demonstrated that the immunopotentiator CVC1302 could improve the humoral immunity induced by the foot and mouth disease virus (FMDV) killed vaccine (KV) with only one dose. Significantly higher FMDV-specific antibody titers and more persistent antibody responses were observed in pigs receiving CVC1302-adjuvanted KV (KV-CVC1302) than in those inoculated with KV alone. In this study, we show that CVC1302 enhances murine IgG responses to FMDV by promoting a potent T follicular helper cell (TFH ) response, which directly controls the magnitude of the germinal center (GC) B cell response. These results indicate a need for studies to assess the capacity of CVC1302 to enhance the efficacy of FMDV KV immunization in pigs, and provide new insights into the development of FMDV vaccines.